The Effect of Deformation Temperature on the Yield Stress of Ultrafine-Grained Al-Cu-Zr Alloy Containing Grain Boundary Nanoprecipitates - Mikhail Yu. Gutkin; Tatiana S. Orlova; Nikolai V. Skiba (Metals, 2023)
A theoretical model is suggested that describes the effect of deformation temperature on the yield stress of an ultrafine-grained (UFG) Al-Cu-Zr alloy structured with severe plastic deformation. Within the model, nanoprecipitates (NPs) of Al2Cu act as sources of lattice dislocations in the presence of a number of extrinsic grain-boundary dislocations (EGBDs) near the NPs. It is shown that the number of EGBDs near the NPs decreases with a drop in the deformation temperature that increases the yield stress of the Al-Cu-Zr alloy. The proposed model is in good quantitative agreement with available experimental results.